Effectiveness of Supervision of 3 Kg LPG Gas Distribution by the Trade, Industry and ESDM Office of Kabupaten Sinjai - Yudiarti Nur; Muhammad Suyuti; Abdul Ganie Gaffar; Reski, Reski (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The purpose of this study was to determine the effectiveness of supervision of the distribution of 3 Kg LPG gas by the Department of Trade, Industry and ESDM of Kabupaten Sinjai. The type of research is qualitative. Data collection techniques are interviews, observations, and. The informants used were LPG gas agents, base owners, end consumers, the head of the trade analysis division of the Kabupaten Sinjai Trade Office. The analysis research used in this qualitative research is an interactive analysis technique by means of data reduction, data presentation and conclusions. The results of the study concluded that the Effectiveness of Supervision of the Distribution of 3 Kg LPG Gas by the Department of Industry Trade and ESDM of Kabupaten Sinjai in achieving goals is still less effective, as well as Integrity in supervision is still less effective, while adaptation in supervision is quite good, but the inhibiting factor in the distribution of subsidized 3 Kg LPG gas cylinders is because the base uses an open system in distributing 3 kg LPG gas.